Gibler
Gibler
04-07-2014
Mathematics
contestada
let f(x)=2x-3 and g(x)= -x^2-1 find ( g o f) (x)
Respuesta :
konrad509
konrad509
04-07-2014
[tex]g \circ f=-(2x-3)^2-1=-(4x^2-12x+9)-1=\\ =-4x^2+12x-9-1=-4x^2+12x-10\\[/tex]
Answer Link
kate200468
kate200468
04-07-2014
[tex]f(x)=2x-3\ \ \ and\ \ \ g(x)= -x^2-1\\\\( g \circ f) (x)=g\bigg(f(x)\bigg)=g\bigg(2x-3\bigg)=-(2x-3)^2-1=\\\\=-(4x^2-12x+9)-1=-4x^2+12x-9-1=-4x^2+12x-10[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 25+ )
Otras preguntas
Which sentence contains an infinitive or infinitive phrase? A. Visit us next week and tell us about your trip. B. Tamar is planning to go to the zoo near her
Im so hopeless no one can answer my homework question and its due tommorow :( How much pressure is exerted when air is being compressed?
which agency coordinates the internet's IP addressing and DNS systems?
DNA copying can be done by bacteria or by using
In The Communist Manifesto, Karl Marx hypothesized that capitalism would fail if workers.?
Which is not a compound? 8H2 H2O 6CaO 5HCl
why did the Crown pass so-called Intolerable Acts
Jesse has 5 and 3/4 dozen eggs. How many eggs does Jesse have?
What kind of scholar studies objects left behind by humans?
is 3/47 a rational number